The Logic of External Reform Resistance: Attitudes toward Economic and Political Liberalization in Senegal. Issue 2 (June 2014) - Parke, Dana M.; Fails, Matthew D.
Thanks in large part to survey efforts such as the Afrobarometer, scholars have developed and tested a variety of theoretical models explaining why citizens in sub-Saharan Africa hold supportive or, conversely, dissatisfied attitudes toward the economic and political reforms of the last several decades. Much of this research highlights citizens' rational evaluation of the new regimes' performance as the critical component. In this article, we advance an alternative argument, namely that citizens also care about the origins of these political and economic transformations. When citizens view these changes as externally imposed, they are less likely to develop supportive and satisfied attitudes toward the process of economic reform and democracy. Original interview data from Dakar, Senegal strongly supports our argument. The findings have important implications for a continent where economic and political institutions have long been shaped by outside actors.